Myeloid-Derived Suppressor Cells Dampen Airway Inflammation Through Prostaglandin E2 Receptor 4 - van Geffen, Chiel; Deißler, Astrid; Beer-Hammer, Sandra; Nürnberg, Bernd; Handgretinger, Rupert; Renz, Harald; Hartl, Dominik; Kolahian, Saeed (Frontiers in Immunology, 2021)
Emerging evidence suggests a mechanistic role for myeloid-derived suppressor cells (MDSCs) in lung diseases like asthma. Previously, we showed that adoptive transfer of MDSCs dampens lung inflammation in murine models of asthma through cyclooxygenase-2 and arginase-1 pathways. Here, we further dissected this mechanism by studying the role and therapeutic relevance of the downstream mediator prostaglandin E2 receptor 4 (EP4) in a murine model of asthma. We adoptively transferred MDSCs generated using an EP4 agonist in a murine model of asthma and studied the consequences on airway inflammation. Furthermore, pegylated human arginase-1 was used to model MDSC effector activities. We demonstrate that the selective EP4 agonist L-902,688 increased the number and suppressive activity of MDSCs through arginase-1 and nitric oxide synthase-2. These results showed that adoptive transfer of EP4-primed MDSCs, EP4 agonism alone or arginase-1 administration ameliorated lung inflammatory responses and histopathological changes in asthmatic mice. Collectively, our results provide evidence that MDSCs dampen airway inflammation in murine asthma through a mechanism involving EP4.